Forbes W. Manchester correspondence - Manchester, Forbes W.
Chiefly letters to Manchester from his wife, Rhoda, of Adamsville, Little Compton, R.I., while he served as first mate aboard the whaleship, Henry Kneeland, on a voyage to the Indian and Pacific oceans (1858-1859). Her letters provide details about the home life of a whaling family, events in the community, and news of other whaling vessels. Includes several letters written by Manchester while on the Henry Kneeland as well as a few written in 1869 from Martinique while he served in the coastal trade on a ship carrying lumber. Also includes letters to Manchester from other family members. Most letters are accompanied by typewritten transcripts.
Typewritten transcripts, in part.
Whaler. Born 1829 or 1830.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Manchester, Rhoda -- Correspondence; Manchester family; Manchester family -- Correspondence; Henry Kneeland (Whaleship); Coastwise shipping -- Martinique; Lumber trade -- Martinique; Whaling -- Indian Ocean; Whaling -- Pacific Ocean; Whaling ships; Little Compton (R.I. : Town) -- History; Whalers (Persons)